Comparison of Self-Concept and Self-Perceived School Success of Children with Foster Home or Family Upbringing - Tirpák, Jan; Uhrinová, Miriam (Journal of Education, Technology and Computer Science, 2021)
This study is concerned with comparing the self-concept and self-perceived school success of children aged 10–15 years growing up in foster homes or in family environments. The research was carried out using the standardized Studentʼs Perception of Ability Scale (SPAS) questionnaire (Matějček, Vágnerová, 1992), applied to a sample cohort of 178 selected respondents. The article reflects key aspects relating to this research.